2021
DOI: 10.1111/acel.13360
|View full text |Cite
|
Sign up to set email alerts
|

Single human oocyte transcriptome analysis reveals distinct maturation stage‐dependent pathways impacted by age

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 82 publications
0
50
0
Order By: Relevance
“…This hypothesis is supported by mouse studies showing an effect of obesity on oocyte polarization, reactive oxygen species levels and DNA methylation, including methylation of metabolism-related genes, such as the leptin promotor region [ 44 , 45 ]. In humans, it has been demonstrated that rising BMI affects regulation of oocyte RNA expression and oocyte metabolism [ 35 , 46 , 47 ]. Furthermore, the maternally-inherited genome passively demethylates with each cell-division, reaching the lowest level at the blastocyst stage, whereas the paternally-inherited genome actively demethylates within 8 h after fertilization [ 48 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by mouse studies showing an effect of obesity on oocyte polarization, reactive oxygen species levels and DNA methylation, including methylation of metabolism-related genes, such as the leptin promotor region [ 44 , 45 ]. In humans, it has been demonstrated that rising BMI affects regulation of oocyte RNA expression and oocyte metabolism [ 35 , 46 , 47 ]. Furthermore, the maternally-inherited genome passively demethylates with each cell-division, reaching the lowest level at the blastocyst stage, whereas the paternally-inherited genome actively demethylates within 8 h after fertilization [ 48 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study based on 133 patients (aged 1–35 years) who underwent FP by ovarian tissue cryopreservation found that patients between menarche to 25 years could achieve the highest IVM rates, while women ≥30 years and pre-menarche girls (<6 years) obtained extremely low IVM rates (<10%) [ 134 ]. The changed oocyte maturation capacity in different ages may stem from the epigenetic changes [ 135 ] and differential gene expressions [ 136 , 137 ] of oocytes as they age. Besides, it has been proven that ovaries before puberty contain abnormal follicles with decreased follicle development [ 138 ].…”
Section: Woman’s Agementioning
confidence: 99%
“…This provides arguments to use mitochondrial transfer to improve IVF pregnancy rates in elderly women [ 222 ], even if more data are necessary before an eventual implementation. Globally, age could impact all proteins [ 223 , 224 ] and aneuploidy is only the most accessible defect detected using conventional technologies. In horses, to the author’s knowledge, high throughput analysis of the oocyte is not yet available.…”
Section: Effects Of Maternal Environment In Equine and Humanmentioning
confidence: 99%